P131 VITAMIN D DEFICIENCY MAY BE ASSOCIATED WITH INFLAMMATORY BOWEL DISEASE EXACERBATIONS. (18th January 2018) - Dave, Jenny; Dodds, Kerian; Alsulaimi, Najwan; Almedimigh, Abdulaziz; Fairfield, Bradley; Borum, Marie L
Abstract: Background and Aims: The role of vitamin D in inflammatory bowel disease (IBD) expression is uncertain. However, there has been speculation that vitamin D deficiency can influence exacerbations. This study evaluated vitamin D levels and IBD exacerbations in patients at a university medical center. Methods: A retrospective chart review of all IBD patients at an urban university hospital during a 6 month period. Patient gender, age, vitamin D level and documented exacerbations were obtained. There were no exclusion factors. Vitamin D deficiency was considered to be serum levels of 25-hydroxy-vitamin D <30 ng/ml. Statistical analysis was performed using Fisher Exact Test with significance set at p<0.05. The study was approved by the IRB. Results: Records of 268 patients (158 Crohn's, 109 Ulcerative Colitis, 1 indeterminate) were reviewed. There were 118 males and 150 females with a mean age of 43 years old. 207 (77.2%) patients were tested for vitamin D. 61 of 207 patients (20 males, 41 females) had a period of relapse of which 51 (83.3%) were vitamin D deficient. In the 146 patients without documented relapse, 96 (65%) were vitamin D deficient. There was a significant difference (p=0.011) in the rate of vitamin D deficiency among patients who relapsed compared to those in remission. Conclusions: Vitamin D may have a potential role in the pathogenesis and regulation of IBD. This study revealed that a significant proportion of all IBD patients had low vitamin D. IBD patients with exacerbations were more likely to be vitamin D deficient than those in remission which may support the hypothesis that vitamin D deficiency has a role in IBD expression. While this study is limited by retrospective design, size and single institutional design, the results can serve as a foundation for future research evaluating the influence of vitamin D in IBD.